2022
DOI: 10.1038/s41598-021-04290-9
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between delayed luminescence emission and mitochondrial status in Saccharomyces cerevisiae

Abstract: Delayed luminescence (DL) is gradually used in various detection of biological systems as a rapid detection technique, however, its biological mechanism was still not clear. In this study, a new model of DL detection system for liquid biological samples is established to investigate the DL emission of Saccharomyces cerevisiae cells cultured in different glucose concentrations. We analyzed the relationship between the DL emission and cell growth, cell vitality, mitochondrial morphology, mitochondrial DNA (mtDN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It was observed that ASTA, for its antioxidant ability, is able to re-establish the oxidative status modified by Aβ exposure in OECs to the control levels. Recent experimental work investigated the relationship between DL and mitochondrial status in Saccharomyces cerevisiae [ 41 ], while the effects of different agents with mitochondrial target on DL from different cells were also evaluated [ 21 , 22 , 23 , 24 , 25 ]. In the present study, the presence of Aβ peptide, especially the toxic fragment, affects DL response.…”
Section: Discussionmentioning
confidence: 99%
“…It was observed that ASTA, for its antioxidant ability, is able to re-establish the oxidative status modified by Aβ exposure in OECs to the control levels. Recent experimental work investigated the relationship between DL and mitochondrial status in Saccharomyces cerevisiae [ 41 ], while the effects of different agents with mitochondrial target on DL from different cells were also evaluated [ 21 , 22 , 23 , 24 , 25 ]. In the present study, the presence of Aβ peptide, especially the toxic fragment, affects DL response.…”
Section: Discussionmentioning
confidence: 99%
“…The industrial instant dry yeast S. cerevisiae (Angel Yeast CO. Ltd., China) was used in this study. This commercial yeast strain has been isolated and purified by multigeneration monoclonal cloning; it is a fast-growing, vigorous and stable strain and has been previously used in many experiments in our laboratory [ [25] , [26] , [27] ]. The yeast cells were cultured to logarithmic phase in YPD medium (1% yeast extract, 2% tryptone, and 2% D- (+)-glucose), and a certain number of yeast cells were harvested and stored in a refrigerator at 4 °C for more than 24 h before use.…”
Section: Methodsmentioning
confidence: 99%
“…Meanwhile, in some studies, yeast was proposed to be a sensitive and versatile model system that could be used for further study of DL [ 23 , 24 ]. Therefore, we used the yeast S. cerevisiae as a model organism for related research, such as using DL to detect oxidative stress in yeast cells [ 25 ], and demonstrated that DL can be used as an indicator of mitochondrial status under different glucose supply conditions [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed luminescence (DL), a light-induced photon emission, is detectable for some seconds after excitation, and was used in several fields of application: Chen et al used it to differentiate serum samples from healthy persons and persons with leukemia, to indicate the functional state of biological systems [1]; structural properties of, e.g., glucose polymers were studied by Grasso et al [2]; mitochondrial respiration by Baran et al [3]; mitochondrial morphology and metabolism by Tian et al [4]; and bioactivity based quality parameters of herbal medicines were evaluated by Sun et al [5]. Differences between organic and conventional products were shown by FES measurements, e.g., for eggs by Köhler and Egerer [6,7], and for milk by Wohlers and Stolz [8].…”
Section: Introductionmentioning
confidence: 99%
“…As spectroscopic techniques are gaining importance, and, e.g., mid-infrared spectroscopy of milk samples was proposed to be useful to predict energy efficiency in individual dairy cows [23,24], or to estimate methane emission level of individual cows [25], delayed luminescence may also be used, as DL is related to energy-related metabolism in mitochondria [3,4]. So, it was of interest whether the FES provides a useful tool to evaluate the level of cow-individual milk samples and whether different diets and temperature conditions affect the DL of the milk.…”
Section: Introductionmentioning
confidence: 99%